Vaccination with a live multi-gene deletion strain protects horses against virulent challenge with Streptococcus equi. Issue 9 (25th February 2015) - Robinson, Carl; Heather, Zoe; Slater, Josh; Potts, Nicola; Steward, Karen F.; Maskell, Duncan J.; Fontaine, Michael C.; Lee, Jeong-Jin; Smith, Ken; Waller, Andrew S.
Graphical abstract